2015
DOI: 10.4103/2231-0762.151978
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience and its association with weight status among 8-year-old children in Qingdao, China

Abstract: Objectives:Childhood obesity/underweight status and caries are both important public health problems. This study aims to investigate the caries status and its association with body weight in 8-year-old children in Qingdao, China.Materials and Methods:We initiated a cross-sectional investigation on 744 children aged 8 years during the Oral Health Survey in 2012. Dental caries assessments were carried out and weight status was recorded accordingly. The resulting caries status including caries prevalence, dmft (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 18 publications
3
33
0
2
Order By: Relevance
“…A cross-sectional study conducted by Alkarimi et al in Saudi Arabian children age 6-8 years old suggested an inverse linear association between dental caries and anthropometric outcomes [ 20 ]. A recent Chinese study among 744 8-year-old children also reported a weak negative association between caries severity and weight status [ 40 ]. In accordance with those findings, we also found that caries-free children were more overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted by Alkarimi et al in Saudi Arabian children age 6-8 years old suggested an inverse linear association between dental caries and anthropometric outcomes [ 20 ]. A recent Chinese study among 744 8-year-old children also reported a weak negative association between caries severity and weight status [ 40 ]. In accordance with those findings, we also found that caries-free children were more overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, children with pufa scores should be characterized to be at high caries risk for early caries onset in permanent teeth. Presenting only dmft data to decision makers leaves them unaware of the severity and associated consequences of untreated caries on general and dental health [ 10 , 42 ]. Therefore, for the first time, our study gathered data on odontogenic infections as consequences of untreated dental caries in 5- and 8-year-old German children by using the pufa index.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the prevalence of overweight children under the age of 5 years worldwide was estimated to be over 41 million . In this context, common predisposing factors between dental caries and overweight/obesity have led researchers to investigate this association …”
Section: Introductionmentioning
confidence: 99%